Tekeningen van kinderen met naam. - Feys, Liesbeth; Van Rompaey, Stefanie (s.l. : Liesbeth Feys & Pleasure Island, 2022)
Meulenijzer, Amber ; Brugni, Anne ; Van Kerckhoven, Anne-Mie ; De Clercq, Anouk ; Gillain, Céline ; Arrouy, Chloé ; Ronse, Elien ; Pepermans, Eliza ; Claus, Eva ; Van Coppenolle, Fran ; Ketelers, Inge ; Baeckelandt, Jolijn ; Heck, Kati ; Vandorpe, Leen ; Feys, Liesbeth ; Van Heuverswijn, Liesbeth ; Vlaemminck, Lisa ; Delanghe, Louise ; Mabesoone, Melissa ; Esi, Nana ; Mabesoone, Natasja ; de Vroome, Nina ; Van Aerde, Sietske ; Nys, Sophie ; Mannaerts, Valérie
boek